On the syntax of the Persian classical narrative poetry: constructions with a past participle in the Shāhnāme - Orsatti, Paola (Journal of Iranian Linguistics, 2024)
This paper aims to describe a particular syntactic construction: that of dependent constructions (clauses, phrases) with a verb in the form of a past participle. Examples of them are mainly taken from Ferdowsi’s Shāhnāme and texts of early poetry, where they represent a prominent and well-attested linguistic phenomenon, but examples from early prose texts have also been given. In the Shāhnāme and early poetry texts, constructions with a past participle are usually placed after a clause with a finite verb in the past tense. They are endowed with a series of syntactic and semantic functions which are not always distinguishable from each other, such as adnominal relativizing, or adverbial modification through phrases or clauses, or predicative complement to the verb. Of these, only participial constructions with an adverbial value, mainly expressing time, but also manner, cause, and other relations, continue up to the present, though in a more rigid form: they are placed before the main clause, and have the value of a subordinate adverbial clause indicating anteriority to the action of the main clause.
Keywords: Shāhnāme; Early and Classical New Persian; participial constructions; past participle; absolute constructions; predicative usages; adverbial clauses